2015
DOI: 10.1001/jamaophthalmol.2014.4447
|View full text |Cite|
|
Sign up to set email alerts
|

Decadelong Profile of Women in Ophthalmic Publications

Abstract: istorically, all surgical subspecialties, including ophthalmology, have been male-dominated fields. 1,2 Potential reasons for this occurrence include lack of opportunity, lack of role models, lack of exposure to surgical fields, and considerations of work-life balance. 1,2 During the past decade, there has been an increase in the number of women surgical residents in the United States commensurate with the increase in women graduating from medical schools. 3,4 At the same time, it is evident that women in opht… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 21 publications
5
58
2
Order By: Relevance
“…Within that time, none of these journals ever had a female editor in chief. 17,18 Like other surgical subjects, ophthalmology has historically been male dominated. 19,20 The pipeline problem 21 describes the phenomenon that despite the increasing number of women entering medicine during the past decade, 22 there is no corresponding increase in women in leadership positions.…”
Section: Average Integration Of Womenmentioning
confidence: 99%
“…Within that time, none of these journals ever had a female editor in chief. 17,18 Like other surgical subjects, ophthalmology has historically been male dominated. 19,20 The pipeline problem 21 describes the phenomenon that despite the increasing number of women entering medicine during the past decade, 22 there is no corresponding increase in women in leadership positions.…”
Section: Average Integration Of Womenmentioning
confidence: 99%
“…A female physician might work fewer hours and see fewer patients during child-rearing years but might increase professional productivity later in life. Because the percentage of women in ophthalmology is much larger among young ophthalmologists, 5 the data in the study by Reddy et al 1 might be skewed toward women who are in childbearing years. An analysis of productivity and physician sex over time would illuminate this question.…”
Section: Discussionmentioning
confidence: 97%
“…Between 2005 and 2014, a total of 37% of candidates taking the American Board of Ophthalmology Written Qualifying Examination were women. 21 While the present study was not designed to determine what obstacles women in ophthalmology face in the context of parallel disparity in authored publications, 5 federal research funding, 6 industry advisory roles, 22 and editorial advancement, 7,23 there is face validity to the position that women have fewer opportunities to pursue the same economic prospects as men. This finding warrants formal attention.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, an observational study conducted to analyze women's participation in original articles and editorials on three ophthalmology journals, which comprised past ten years as academic publications. The study found the participation of female researchers was 671 original articles with 89 editorials 16 . Moreover, a huge study was conducted in ophthalmologic journals indexed in Web of Science (WoS) from 2008 to 2018 to determine the representation of female authorship according to first name, under the title -Sex Disparities in Ophthalmic Research: A Descriptive Bibliometric Study on Scientific Authorships‖.…”
Section: Resultsmentioning
confidence: 99%